Pengaruh Likuiditas, Risiko Bisnis dan Struktur Aktiva terhadap Struktur Modal - afa afa; Shadrina Hazmi (AL-QARDH, 2021)
The aim of this study was to find out the effect of liquidity, business risk, and asset structure to capital structure in consumer goods industry manufacturing companies listed on the Bursa Efek Indonesia for the period 2015-2019. The ratio used to measure the liquidity variable is the current ratio, the business risk variable is measured by BRISK, and the asset structure variable is measured by the fixed asset ratio. The sampling technique used was purposive sampling method. This research was conducted with 19 samples of companies in the consumer goods industry sector. The results show that the liquidity variable has a significant effect on the capital structure of manufacturing companies in the consumer goods industry sector listed on the BEI for the period 2015-2019, meanwhile, the business risk and asset structure variables have no significant effect on the capital structure of manufacturing companies in the consumer goods industry listed on the BEI for the period 2015-2019